Efektivitas Implementasi Program Bantuan Sosial bagi Masyarakat Terdampak Covid-19 pada Masa PPKM Darurat di Kota Bandung - Faadhilah Febriyanti Umar, Afifah; Rosarie Harni Triastuti, Maria (STISIPOL Raja Haji, 2023)
The purpose of the social assistance program in the city of Bandung is to help families who do not receive any assistance at all during the pandemic, especially during Emergency PPKM. However, the existence of this social assistance program poses many problems. Such as the results of data collection carried out, the process of inappropriate criteria and the process of program distribution. This study aims to determine the effectiveness of the implementation of social assistance programs for communities affected by Covid-19 during the emergency PPKM in Bandung City. This study uses qualitative methods with data collection techniques using interviews and document studies. Based on the results of research and analysis that has been carried out, it can be concluded that (1) changes in system operations on process quality indicators are quite effective but the target criteria are not fully appropriate and on indicators of achievement of results are quite effective, but there is a delay in the distribution of assistance from Bank BJB (2) changes in the target group on the process quality indicators are quite effective, but the amount of assistance provided does not meet daily needs and on the indicators of achievement of results is quite effective but the benefits of assistance are felt only for a moment.